Dynamical masses and mass-to-light ratios of resolved massive star clusters – II. Results for 26 star clusters in the Magellanic Clouds. Issue 3 (17th April 2021) - Song, Ying-Yi; Mateo, Mario; Bailey, John I; Walker, Matthew G; Roederer, Ian U; Olszewski, Edward W; Reiter, Megan; Kremin, Anthony
ABSTRACT: We present spectroscopy of individual stars in 26 Magellanic Cloud (MC) star clusters with the aim of estimating dynamical masses and V -band mass-to-light ( M / LV ) ratios over a wide range in age and metallicity. We obtained 3137 high-resolution stellar spectra with M2FS on the Magellan /Clay Telescope. Combined with 239 published spectroscopic results of comparable quality, we produced a final sample of 2787 stars with good quality spectra for kinematic analysis in the target clusters. Line-of-sight velocities measured from these spectra and stellar positions within each cluster were used in a customized expectation-maximization (EM) technique to estimate cluster membership probabilities. Using appropriate cluster structural parameters and corresponding single-mass dynamical models, this technique ultimately provides self-consistent total mass and M / LV estimates for each cluster. Mean metallicities for the clusters were also obtained and tied to a scale based on calcium IR triplet metallicities. We present trends of the cluster M / LV values with cluster age, mass, and metallicity, and find that our results run about 40 per cent on average lower than the predictions of a set of simple stellar population (SSP) models. Modified SSP models that account for internal and external dynamical effects greatly improve agreement with our results, as can models that adopt a strongly bottom-light IMF. To the extent that dynamical evolution must occur, a modified IMF is not required to match data and models. In contrast, a bottom-heavy IMF is ruled out for our cluster sample as this would lead to higher predicted M / LV values, significantly increasing the discrepancy with our observations.